2003
DOI: 10.1093/annonc/mdg277
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and aven: two distinct antiapoptotic signals in acute leukemias

Abstract: Both survivin and aven are important antiapoptotic signals in acute leukemias, and the association between extramedullary involvement, CD7 expression and CD34 expression, which are important poor prognostic indicators in acute leukemias, suggests that survivin and/or aven may be novel prognostic indicators in acute leukemias. Further studies with a higher number of patients will be more informative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
1
26
0
3
Order By: Relevance
“…We used flowcytometry for detection of intracellular survivin and determine its MFI on leukemic blast. In our 30 ALL patients, expression of survivin above the background level in normal hematopoietic cells was detected in 19 (63.3%) of the patients this is similar to what was reported by Troeger et al [20], who detect over expression of survivin in 65% of pediatric ALL patients and higher than Paydas et al [24], who study survivin in 56 leukemia patients (37 AML and 28 ALL) they detected high survivin in 54% of the patients. Survivin expression was significantly elevated in pediatric ALL with a median MFI level of 183 (0-1390) when compared with the level in control group (P = 0.003) this in agreement with Troeger et al [20], and with what reported previously as surviving was expressed in all AML cell lines and most of the leukemia cells and/or bone marrow cells [11].…”
Section: Discussionsupporting
confidence: 89%
“…We used flowcytometry for detection of intracellular survivin and determine its MFI on leukemic blast. In our 30 ALL patients, expression of survivin above the background level in normal hematopoietic cells was detected in 19 (63.3%) of the patients this is similar to what was reported by Troeger et al [20], who detect over expression of survivin in 65% of pediatric ALL patients and higher than Paydas et al [24], who study survivin in 56 leukemia patients (37 AML and 28 ALL) they detected high survivin in 54% of the patients. Survivin expression was significantly elevated in pediatric ALL with a median MFI level of 183 (0-1390) when compared with the level in control group (P = 0.003) this in agreement with Troeger et al [20], and with what reported previously as surviving was expressed in all AML cell lines and most of the leukemia cells and/or bone marrow cells [11].…”
Section: Discussionsupporting
confidence: 89%
“…The genetic lesion identified in AVEN is of potential interest because this gene impairs Apaf-1-mediated activation of caspases, and thus apoptosis (39). We and others (9,(15)(16)(17)40) have previously identified other (non-Bcl-2) antiapoptotic survival pathways as being particularly important in MPM tumorigenesis and drug resistance, and AVEN was recently implicated in acute leukemias (41). Elucidating the functional relevance of the previously uncharacterized variant alleles rendered homozygous by LOH in MPM (Table 3) is a promising avenue for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Furthermore, evidence is now accumulating that the expression level of survivin contributes to the clinical outcome of tumors, including prognosis, susceptibility to anti-cancer drugs, and malignant behavior. 56,57 Recent studies indicate the potential clinical relevance of survivin quantified by real-time PCR in ATL. 58 Selectivity of expression and biological importance render survivin an attractive target for treatment, but the 3-dimensional structure of survivin shows no obvious opportunity for drug design.…”
Section: Discussionmentioning
confidence: 99%